Mitragynine inhibits hippocampus neuroplasticity and its molecular mechanism - Yunusa, Suleiman; Hassan, Zurina; Müller, Christian P. (Pharmacological Reports, 2023)
Background: Mitragynine (MIT), the primary indole alkaloid of kratom (Mitragyna speciosa), has been associated with addictive and cognitive decline potentials. In acute studies, MIT decreases spatial memory and inhibits hippocampal synaptic transmission in long-term potentiation (LTP). This study investigated the impacts of 14-day MIT treatment on hippocampus synaptic transmission and its possible underlying mechanisms. Methods: Under urethane anesthesia, field excitatory post-synaptic potentials (fEPSP) of the hippocampal CA1 region were recorded in the Sprague Dawley (SD) rats that received MIT (1, 5, and 10 mg/kg), morphine (MOR) 5 mg/kg, or vehicle (ip). The effects of the treatments on basal synaptic transmission, paired-pulse facilitation (PPF), and LTP were assessed in the CA1 region. Analysis of the brain's protein expression linked to neuroplasticity was then performed using a western blot. Results: The baseline synaptic transmission's amplitude was drastically decreased by MIT at 5 and 10 mg/kg doses, although the PPF ratio before TBS remained unchanged, the PPF ratio after TBS was significantly reduced by MIT (10 mg/kg). Strong and persistent inhibition of LTP was generated in the CA1 region by MIT (5 and 10 mg/kg) doses; this effect was not seen in MIT (1 mg/kg) treated rats. In contrast to MIT (1 mg/kg), MIT (5 and 10 mg/kg) significantly raised the extracellular glutamate levels. After exposure to MIT, GluR-1 receptor expression remained unaltered. However, NMDAε2 receptor expression was markedly downregulated. The expression of pCaMKII, pERK, pCREB, BDNF, synaptophysin, PSD-95, Delta fosB, and CDK-5 was significantly downregulated in response to MIT (5 and 10 mg/kg) exposure, while MOR (5 mg/kg) significantly raised synaptophysin and Delta fosB expression. Conclusion: Findings from this work reveal that a smaller dose of MIT (1 mg/kg) poses no risk to hippocampal synaptic transmission. Alteration in neuroplasticity-associated proteins may be a molecular mechanism for MIT (5 and 10 mg/kg)-induced LTP disruption and cognitive impairments. Data from this work posit that MIT acted differently from MOR on neuroplasticity and its underlying mechanisms. Graphical abstract: [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2023-11-17
Keywords: Cognitive deficit; fEPSP; Hippocampal synaptic transmission; Mitragynine; Western blot